2019
DOI: 10.1177/1479164119874469
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced early molecular and functional changes in aortic heart valves in a murine model of atherosclerosis

Abstract: Diabetes contributes directly to the development of cardiovascular aortic valve disease. There is currently no drug therapy available for a dysfunctional valve and this urges the need for additional research to identify distinctive mechanisms of cardiovascular aortic valve disease evolution. The aim of this study was to evaluate changes of valvular aortic lesions induced in a hyperlipemic ApoE−/− mouse model by early type 1 diabetes onset (at 4 and 7 days after streptozotocin induction). The haemodynamic valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…In this experimental model, mean glycemia values for CIT control groups were 144.3 ± 5.2 mg/dl for CIT4 and 144.3 ± 5.2 mg/dl for CIT7, while for STZ groups, these were 219.1 ± 18.2 mg/dl for STZ4 and 271.8 ± 25.8 mg/dl for STZ7 as previously published 21 . Also, the duration of the atherogenic diet of 4 or 7 days significantly interacted with diabetes to increase plasma cholesterol and triglyceride concentration and induce early molecular and functional changes in aortic heart valves 21 .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In this experimental model, mean glycemia values for CIT control groups were 144.3 ± 5.2 mg/dl for CIT4 and 144.3 ± 5.2 mg/dl for CIT7, while for STZ groups, these were 219.1 ± 18.2 mg/dl for STZ4 and 271.8 ± 25.8 mg/dl for STZ7 as previously published 21 . Also, the duration of the atherogenic diet of 4 or 7 days significantly interacted with diabetes to increase plasma cholesterol and triglyceride concentration and induce early molecular and functional changes in aortic heart valves 21 .…”
Section: Resultssupporting
confidence: 81%
“…In our experiments, aortic valves from mice fed 7 days with a high-fat diet showed an increased number of CD34 positive cells compared with animals on shorter diet lengths and their diabetic counterparts. In a previous article, we showed that at this time point, VCAM-1 and P-selectin are significantly increased in the aortic valve, a hallmark of endothelium activation 21 . This probably leads to EPC recruitment from the circulation in dyslipidemic controls (CIT4 and CIT7 groups) but, due to their lower number and lower VCAM-1 ligand, α 4 β 1 , EPCs from diabetic animals are recruited less efficiently.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…CAVD is accelerated in diabetes [ 21 , 22 , 23 ]. Recently, it was shown an increased expression of inflammatory and pro-osteogenic markers in the aortic valves of diabetic hyperlipemic ApoE-deficient mice as compared with non-diabetic hyperlipemic controls [ 24 ]. Moreover, elevated mRNA Runx2 level was determined in the aortic tissues of diabetic LDLr−/−/ApoB100/100/IGF-II mice as compared to non-diabetic or wild type C57BL/6 control mice [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that nanocarriers designed for Runx2 RNA interference could halt or reverse the osteodifferentiation of human VIC exposed to high glucose concentrations or/and osteogenic factors. Previously, we have developed dendrimer-like structures of branched low molecular weight polyethyleneimine (PEI) (2 kDa) organized around a fullerene (C60) core, able to act as gene vectors, by forming stable polyplexes with plasmid DNA [ 24 ]. For our experiments, we designed nanocarriers consisting of nano-polyplexes formed between the nano-conjugates of C60-PEI and the plasmids containing shRNA sequences specific for Runx2 (shRNA-Runx2).…”
Section: Introductionmentioning
confidence: 99%